“Your sexuality is yours and yours alone”: a reflexive thematic analysis of sexual orientation microaggressions and their impact on LGB emerging adults’ sexual health knowledge and attitudes - Robinson, Ty A.; Coleman, Taylor M.; Carmack, Chakema (Frontiers in Public Health, 2025)
IntroductionLesbian, gay, and bisexual (LGB) adults often experience cissexism, heterosexism, and other forms of discrimination, which, as a result, leaves LGB adults vulnerable to identity-related victimization such as sexual orientation microaggressions (SOMs). These derogatory, hostile, and homophobic insults can lead to adverse mental and physical health outcomes for this minoritized group. While research has established taxonomies related to SOMs and their impact on the mental health and identity development of LGB people, little research has addressed the systemic influence SOMs have on sexual health knowledge and risk-related sexual behavior.MethodsThe present study conducted four focus groups with LGB emerging adults (N = 17; M = 20.4 ± 2.4) to understand how their experiences with microaggressions might affect their knowledge and attitudes about sex and sexual risk behavior.ResultsReflexive thematic analysis resulted in four themes as critical aspects of (a) early familial moments, (b) religious persecution about their sexuality, (c) coping and resilience strategies and sexual health, and (d) sexual education and miseducation.DiscussionResults suggest that SOMs greatly influence how LGB individuals view their identity, sexual health, and attitudes toward sexual behavior. Additionally, addressing these microaggressions in the education, family, and healthcare systems may enhance healthcare access and quality and create inclusive environments that encourage equitable experiences early on in one’s identity development. Given that sexual health education begins during the stage of adolescence, future research can utilize these findings to design a study that understands LGB youth experiences of SOMs and how it impacts their identity development, well-being, and sexual health behaviors and attitudes.